Comparison of Energy Consumption of Wireless Sensor Network at Various Topology Deployment: Array, Grid, and Random - Ari Sriyanto Nugroho; Ipang Prasojo (Politeknik Negeri Semarang, 2016)
This paper is review wireless sensor network and it’s energy consumption at different deployment methods. Wireless Sensor Networks (WSN) are emerging with many applications, because of the advances in large scale wireless communications. These networks are deployed to serve single objective application, with high optimization requirements such as power saving. The WSN design problem is of high complexity, and requires robust methodologies, including simulation support. We use NS2 as simulation program for this model. In this paper, the authors compare the energy consumption on three different deployment methods of WSN. These deployment methods refer to topology deployment. In this simulation, we deploy WSN on grid, array, and random topology. We use different numbers of WSN nodes for showing the scalability. We use AODV as routing protocol and CBR as the traffic. After that, we compare the energy consumption that consume by that networks. Based on simulation result, the array topology is the best topology for deployment. This topology is the lowest on energy consumption, 0.560%.